2021
DOI: 10.1177/09722629211011811
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Cointegration Between Economic Growth and Financial Development in Emerging Asian Economy: Evidence from India

Abstract: The present article examines the relationship between economic growth and financial development in the context of Indian economy over the period of 15 years from June 2003 to February 2018. The study employs cointegration test, involving Johansen Juselius Cointegration and autoregressive distributed lag (ARDL) Bounds test approach to ascertain the long-run relationship between financial development and economic growth. The study further employs fully modified ordinary least squares—OLS—(FMOLS), dynamic OLS (DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The supply-leading hypothesis suggests that financial development drives economic growth, indicating a unidirectional causality from finance to economic growth. For instance, Tripathy and Mishra (2021) confirmed the supply leading hypothesis, showing unidirectional causality from financial development to economic growth in the Indian economy. The demand-following hypothesis presents an alternative viewpoint to the supply-leading hypothesis.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…The supply-leading hypothesis suggests that financial development drives economic growth, indicating a unidirectional causality from finance to economic growth. For instance, Tripathy and Mishra (2021) confirmed the supply leading hypothesis, showing unidirectional causality from financial development to economic growth in the Indian economy. The demand-following hypothesis presents an alternative viewpoint to the supply-leading hypothesis.…”
Section: Introductionmentioning
confidence: 52%
“…As businesses flourish and the economy prospers, the demand for financial products such as loans, investments, and insurance rises, prompting financial institutions to expand to meet these growing needs. Moreover, economic growth often leads to higher incomes and accumulated wealth for individuals and households, encouraging greater saving and investment activity, thus boosting the demand for financial services (Tripathy & Mishra, 2021). Furthermore, the improved economic climate can stimulate a heightened risk appetite, motivating people to seek investment opportunities and financial products that offer potentially higher returns.…”
Section: Introductionmentioning
confidence: 99%
“…Boachie et al (2020) using ARDL estimation technique from 1960–2013 found that financial development and trade openness has encouraged private sector investment in India. Tripathy and Mishra (2021) looked into the connection between financial development and economic growth for India from 2003 to 2018. The study’s findings point to a long-term connection between financial development and economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%
“…But India's global ascendancy across the economic landscape of the world led to financial integration of Indian market with other developing and emerging nations also. Many studies (like Sehgal et al, 2019;Kumar & Aurora, 2020;Tripathy & Mishra, 2021) tried to explore the possibility of financial integration of Indian market with selected emerging markets. But unfortunately, researchers could not get any consensus.…”
Section: Introductionmentioning
confidence: 99%